Diretoras brasileiras e a representação da mulher em documentários dos anos 1980 - Esperança, Hanna Henck Dias (2020)
In the 1980s, women occupied a significant portion of the making of short and medium-length documentaries in Brazil, with a very diverse production in terms of narrative and language. In view of the small amount of research on the aforementioned films and the difficulty of accessing the relevant data and movies, this work aims to contribute toward making this production find greater repercussion and recognition in the field of studies devoted to Brazilian cinema. Through film analysis and with texts from many different areas, we discuss eight documentaries that vary between short and medium-length films: "Mulheres da terra" (Marlene França, 1985), "Marias da castanha" (Edna Castro and Simone Raskin, 1987), "Sulanca: a revolução econômica das mulheres de Santa Cruz do Capibaribe" (Kátia Mesel, 1986), "Como um olhar sem rosto (As presidiárias)" (Maria Inês Villares, 1983), "Mulheres da Boca" (Cida Aidar and Inês Castilho, 1982), "Retratos de Hideko" (1981) e "Hia sá sá – hai yah" (1985), both by Olga Futemma, and "Meninas de um outro tempo" (Maria Inês Villares, 1986). These films put in perspective the female representation in the documentary and the role of women in society, articulating the feminist, social, political and cinematographic debate of the time.